Art, Myth and Memory: An Investigation into the Relationship Between Ancient Myths, Collective and Cultural Memory and the Visual Arts - Alessandra Campoli (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2020)
This paper aims at investigating the relationship between collective and cultural memory, myth, and contemporary art practice. Artists in the past have relied on the power of myth to visually speak to their audience, re-presenting myths in an illusionistic way. Today art is not conventionally telling stories anymore and is disentangled from the need for mimesis. How has the relation between art and myth changed outside the framework of representational art? Is the connection between myth and collective and cultural memory used in contemporary art practice? How do art and myth intersect today?